Characteristics of Cardiac Rhythm and Conduction Abnormalities Diagnosed in Mobile Emergency Units in Central Romania - Masalar Aurelian Lucian; Linga Eugen; Crișan Sorin; Rădulescu Dan; Buzdugan Elena (Journal of Cardiovascular Emergencies, 2017)
Background: Cardiac arrhythmias and conduction abnormalities are frequently identified by emergency medical service staff in patients requesting emergency services.